DAMPAK TINGKAT KEPERCAYAAN ELEKTRONIK, KEPUASAN ELEKTRONIK, LOYALITAS ELEKTRONIK DAN KUNJUNGAN KEMBALI SITUS PADA TINDAK KEJAHATAN SIBER (CYBER CRIME) PERBANKAN - Muhammad Adhitya Wardhana; Nur Hayati; Yunus Mustaqim (Universitas Muhammadiyah Kudus, 2023)
Cyber crime is always lurking, especially in the banking sector, there are various types of cyber crime. Of course, this cyber crime does not only have an impact on banking, but also affects its customers. This crime will certainly affect customer trust, customer satisfaction levels, customer loyalty and customer return visits. In this research, the researcher used a qualitative method with a descriptive approach using document review, various cybercrime news sites, to carry out an in-depth analysis of whether this cybercrime had an impact that spread to other impacts.